# C u v is not a vector d the dot product of a scalar k

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: √ = 2 2π π sin θ(1 − cos θ)3/2 dθ = 0 2√ 2 2π (1 − cos θ)5/2 5 π = 32π/5 0 π 2πa sin(θ)a dθ = 4πa2 30. S = 0 31. (a) r3 cos3 θ − 3r2 cos θ sin θ + r3 sin3 θ = 0, r = π /(2n) 32. (a) A = 2 0 πa2 12 a cos2 nθ dθ = 2 4n 3 cos θ sin θ cos3 θ + sin3 θ π /(2n) (b) A = 2 0 2 (c) πa 1 × total area = 2n 4n (d) πa2 12 a cos2 nθ dθ = 2 4n 1 πa2 × total area = n 4n 33. If the upper right corner of the square is the point (a, a) then the large circle has equation r = and the small circle has equation (x − a)2 + y 2 = a2 , r = 2a cos θ, so π /4 √ 1 (2a cos θ)2 − ( 2a)2 dθ = a2 = area of square. area of crescent = 2 2 0 √ 2a Exercise Set 12.4 2π 34. A = 0 422 1 (cos 3θ + 2)2 dθ = 9π/2 2 π /2 35. A = 0 1 4 cos2 θ sin4 θ dθ = π/16 2 1 3 -3 3 0 1 –1 -3 EXERCISE SET 12.4 1. (a) (c) 4px = y 2 , point (1, 1), 4p = 1, x = y 2 a = 3, b = 2, y2 x2 + =1 9 4 (b) −4py = x2 , point (3, −3), 12p = 9, −3y = x2 (d) a = 3, b = 2, x2 y2 + =1 4 9 (e) asymptotes: y = ±x, so a = b; point (0, 1), so y 2 − x2 = 1 (f ) asymptotes: y = ±x, so b = a; point (2, 0), so x2 y2 − =1 4 4 2. (a) part (a), vertex (0, 0), p = 1/4; focus (1/4, 0), directrix: x = −1/4 part (b), vertex (0, 0), p = 3/4; focus (0, −3/4), directrix: y = 3/4 √ √ √ (b) part (c), c = a2 − b2 = 5, foci (± 5, 0) √ √ √ part (d), c = a2 − b2 = 5, foci (0, ± 5) √ √ √ (c) part (e), c = a2 + b2 = 2, foci at (0, ± 2); asymptotes: y 2 − x2 = 0, y = ±x √ √ √ √ y2 x2 − = 0, y = ±x part (f), c = a2 + b2 = 8 = 2 2, foci at (±2 2, 0); asymptotes: 4 4 y 3. (a) y (b) 5 3 y= F ( 3 , 0) 2 -3 x x -5 3 x=– 3 -3 2 5 -5 y 4. (a) 9 4 ( 9 F 0, – 4 ) y (b) F(0, 1) ( 5 2 F – ,0 ) x x y = –1 x= 5 2 423 Chapter 12 y 5. (a) x= 6 y (b) 1 2 x -4 V(–2, –2) V(2, 3) () 7 F 2, 3 y=– 7 4 ( F –2, – 9 x 4 ) -4 6 y 6. (a) x= y (b) 23 4 F x y= F ( 9 , –1) 4 (1 , 3 ) 22 1 2 x V(4, –1) V y 7. (a) 4 (b) ( 2) x=– ( 1 , 1) 2 y 9 4 V 2, 5 4 V(–2, 2) ( ) 7 F –4, 2 y=3 F(2, 2) x x 2 4 8. (a) y x = –9 y (b) 2 V(–4, 3) ( 7 2 F – ,3 ( F –1, ) V (–1, 1) 17 16 x y= 15 16 x 9. (a) c2 = 16 − 9 = 7, c = √ 7 (b) c2 = 9 − 1 = 8, c = y (0, 3) (–4, 0) y2 x2 + =1 1 9 (√7, 0) √ 8 y (0, 3) (0, √ 8) x (4, 0) x (– √7, 0) (0, –3) (–1, 0) (1, 0) (0, – √ 8) (0, –3) ) Exercise Set 12.4 424 10. (a) c2 = 25 − 4 = 21, c = (0, 5) √ 21 (b) y y2 x2 + =1 9 4 √ c2 = 9 − 4 = 5, c = 5 (0, √ 21) y (0, 2) x (–2, 0) (√ 5, 0) (–3, 0) (2, 0) x (0, – √ 21) (0, –5) 11. (a) (3, 0) (– √ 5, 0) (y − 3)2 (x − 1)2 + =1 16 9 √ c2 = 16 − 9 = 7, c = 7 (b) (0, –2) (y + 1)2 (x + 2)2 + =1 4 3 c2 = 4 − 3 = 1, c = 1 y y (1 – √7, 3) (1, 6) (–2, –1 + √ 3) (1 + √7, 3) x (–3, –1) (–3, 3) (0, –1) (–4, –1) (5, 3) (–1, –1) x (–2, –1 – √ 3) (1, 0) 12. (a) (y − 5)2 (x + 3)2 + =1 16 4 √ c2 = 16 − 4 = 12, c = 2 3 (b) (y + 2)2 x2 + =1 4 9 √ c2 = 9 − 4 = 5, c = 5 y (–3 –2 √ 3, 5) y (0, 1) (–3, 7) (0, –2 + √ 5) x (–7, 5) (1, 5) (–3, 3) (–3 +2 √ 3, 5) (–2, –2) (2, –2) x (0, –5) (0, –2 – √ 5) 425 13. (a) Chapter 12 (y − 1)2 (x + 1)2 + =1 9 1 √ c2 = 9 − 1 = 8, c = 8 (b) (y − 5)2 (x + 1)2 + =1 4 16 √ c2 = 16 − 4 = 12, c = 2 3 y y (–1, 9) (–1 – √8, 1) (–1, 2) (–1, 5 + 2 √3) (2, 1) (–3, 5) x (–4, 1) (–1, 0) (1, 5) (–1, 5 – 2 √3) (–1 + √8, 1) x (–1, 1) 14. (a) (y − 3)2 (x + 1)2 + =1 4 9 √ c2 = 9 − 4 = 5, c = 5 (b) (y + 3)2 (x − 2)2 + =1 9 5 c2 = 9 − 5 = 4, c = 2 y (–1, 6) (2, –3 + √5) y (–3, 3) (1, 3) (4, –3) (–1, –3) (0, –3) x (2, –3 – √5) (–1, 3 – √5) (–1, 0) √ 15. (a) c2 = a2 + b2 = 16 + 4 = 20, c = 2 5 y (0, √ 13) y = –2 x 3 (b) y 2 /4 − x2 /9 = 1 √ c2 = 4 + 9 = 13, c = 13 y (0, 2) y= 2x 3 x y = –1 x 2 (–4, 0) y= 1x (4, 0) 2 x (0, – √ 13) x (–1, 3 + √5) (0, –2) (–2 √ 5, 0) (2 √ 5, 0) (5, –3) Exercise Set 12.4 426 16. (a) c2 = a2 + b2 = 9 + 25 = 34, c = √ 34 y (0, √ 34) (0, 3) 3 5 y=– x y= (b) x2 /25 − y 2 /16 = 1 √ c2 = 25 + 16 = 41, c = 41 y 4 5 y=– x 3 x 5x y= 4 x 5 (–5, 0) (5, 0) x (0, – √ 34) (0, –3) (– √41, 0) 17. (a) c2 = 9 + 4 = 13, c = y √ 13 (√41, 0) (b) (y + 3)2 /36 − (x + 2)2 /4 = 1 √ c2 = 36 + 4 = 40, c = 2 10 y – 4 = 2 (x – 2) 3 (2 – √13, 4) (–2, –3 + 2 √10) (2 + √13, 4) (5, 4) y (–2, 3) (–1, 4) x y + 3 = – 3(x + 2) x y + 3 = 3(x + 2) (–2, –9) y – 4 = – 2 (x – 2) 3 (–2, –3 – 2 √10) √ 18. (a) c2 = 3 + 5 = 8, c = 2 2 y+4= y √3 (x – 2) 5 (2, – 4 + 2 √ 2) (b) (x + 1)2 /1 − (y − 3)2 /2 = 1 √ c2 = 1 + 2 = 3, c = 3 y − 3 = −√2(x + 1) y x (–2, 3) (2, – 4 + √ 3) (-1 − √3, 3) (2, – 4 – √ 3) √3 (x – 2) 5 (-1 + √3, 3) x (2, – 4 – 2 √ 2) y+4=– (0, 3) y − 3 = √2(x + 1) 427 Chapter 12 19. (a) (x + 1)2 /4 − (y − 1)2 /1 = 1 √ c2 = 4 + 1 = 5, c = 5 (b) (x − 1)2 /4 − (y + 3)2 /6...
View Full Document

## This document was uploaded on 02/23/2014 for the course MANAGMENT 2201 at University of Michigan.

Ask a homework question - tutors are online